Geleneksel yüzey pürüzlendirme yöntemleri ile dijital olarak kontrol edilebilen er:Yag lazerin mine dokusu üzerindeki mekanik etkilerinin karşılaştırmalı olarak incelenmesi / Comparison of the effects of conventional enamel etching systems and digitally controlled er:Yag laser hand piece on human enamel tissue - Karamehmetoğlu, Hilal (Bezmialem Vakıf University, 2015)
The aim of this study was to compare the bracket bond strenght, AFM and SEM analysis of etched and debonded enamel surfaces using different enamel etching procedures. In this study intact, extracted 98 human maxillary teeth were used. 80 teeth were divided into four groups: Group 1: Acid (37% phosphoric acid), Group 2: Er:YAG laser (120 mJ, 10 Hz., 40% water, 50% air), Group 3: Er,Cr:YSGG laser (45 mJ, 50 Hz., 30% water, 60% air) and Group 4: Xrunner (100 mJ, 10 Hz., 40% water, 50% air, 2-horizontal+2-vertical scanning). After bonding the braces, samples were stored in distilled water at room temperature for 24 hours, and then thermocycling for a total of 5.000 cycles at 5°C – 55°C with a dwell time of 30 seconds was performed. The shear bond strength was measured by using a universal testing machine with a crosshead speed of 0.5 mm per second. After debonding, the amount of resin remaining on the teeth was determined using the adhesive remnant index. SEM and AFM images were taken from all groups one sample each for etched and debonded enamel surfaces. Er:YAG laser group showed the highest shear bond strenght values followed by acid, Xrunner, and Er,Cr:YSGG laser groups. But the difference was not statistically significant among the groups (p=0.148). There were statistically significant differences among the ARI scores of the groups (p<0.001). Acid group showed significantly higher values than laser groups. Our findings reported that enamel etching with acid, Er:YAG, Er,Cr:YSGG and Xrunner showed mean bracket bond strenght values which are above the range of clinically acceptable values in literature.

{{abstract}}
Thesis (Doctoral)--Bezmialem Vakıf University, Ortodonti, Istanbul, 2015
Keywords: Lazerle pürüzlendirme; Makaslama testi; Ortodontik braket; Laser etching; Shear bond strength; Orthodontic braces